Surface characterization and dehydrocyclization activity of Pt/KL catalysts prepared by different methods - Arcoya, Adolfo (2003)
Three Pt/KL-zeolite catalysts containing 1 wt.% of metal were prepared by different procedures: CI-1 and CI-2 by wetness impregnation of the zeolite with aqueous solutions of Pt(NH3)4(OH)2 and Pt(NH3)4(NO3)2, respectively, and CE-3 by ion exchange with a Pt(NH3)4(OH)2 solution. These samples were successively calcined at 573 K and reduced at 773 K. An additional sample, CE-3-n, was obtained from CE-3 by ion-exchange with KNO3. The catalysts were characterized by H2–O2 titration, TPD of NH3, XRD, CO–FTIR and XPS and tested in the dehydrocyclization of n-heptane to toluene at 723 K, 100 kPa, WHSV=3.4 h−1 and H2/nC7=7.3 mol mol−1 in a fixed bed tubular reactor. Characterization results show that Pt dispersion for the ion exchanged samples is higher than for the impregnated ones and CE-3 is the more acidic catalyst. FTIR measurements indicate that the highest population of electron reach platinum species (Ptδ−) is found in CE-3-n, while CE-3 exhibits the highest concentration of electron deficient platinum species (Ptδ+). The order of dehydrocyclization activity, CE-3-n>CI-2>CI-1>CE-3, roughly correlates with that of the intensity of the FTIR bands attributed to Ptδ−. The low selectivity toward toluene of CE-3 is attributed to the protons generated during the reduction of Pt2+ exchanged.